Cognitive precision and expressiveness in stock market communication : a contrastive perspective - Duda, Bozena; Nycz, Krzysztof (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nowadays, economic issues make up a significant part of everyday communication. Daily business news on television and in digital sources, constant contacts with financial institutions – to name a few – only emphasize the omnipresence of the economy in our lives and at the same time confirm that we are inescapably involved in economic processes. The subject matter of the paper is a specific area of business communication, namely stock market communication. Drawing on Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (2003) and the model of schematicity hierarchies of metaphorical concepts by Kövecses (2019), as well as Littlemore’s (2015) and Brdar’s (2019) findings on the functions and regularity of metonymic patterns, we aim to investigate the nature and functions of metonymies and metaphors found to be reflected in stock market communication. Another objective is to present precision and expressiveness in stock market communication achieved through the use of figurative (metaphorical and metonymic) means. In particular, we conducted a qualitative analysis of selected metonymic and metaphorical expressions in three different languages (English, German and Polish) extracted from stock market reports and commentaries. The choice of the contrastive perspective results from Weinrich’s (1976) assumption that languages belonging to the western cultural community should share patterns of conceptualizations. The findings of the analysis conducted seem to show that image schemata and domain levels overlap to a great extent in the three languages under analysis, and cultural variation and differences – if present – occur at the more specific level of frames and/or mental spaces.